2018
DOI: 10.1094/mpmi-09-17-0232-r
|View full text |Cite
|
Sign up to set email alerts
|

Multiple CsrA Proteins Control Key Virulence Traits inPseudomonas syringaepv.tomatoDC3000

Abstract: The phytopathogenic bacterium Pseudomonas syringae pv. tomato DC3000 has a complex Gac-rsm global regulatory pathway that controls virulence, motility, production of secondary metabolites, carbon metabolism, and quorum sensing. However, despite the fact that components of this pathway are known, their physiological roles have not yet been established. Regarding the CsrA/RsmA type proteins, five paralogs, three of which are well conserved within the Pseudomonas genus (csrA1, csrA2, and csrA3), have been found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(91 citation statements)
references
References 70 publications
3
70
0
Order By: Relevance
“…; Table ). We also observed that mutation of the rsmA1 gene alone did not affect GABA utilization, protease activity and pyoverdine production (except a minor increase in motility) (Figs and ), suggesting that RsmA1 plays a very minimal role, as previously reported (Ferreiro et al , ). Based on these results, we mainly focused on RsmA2, RsmA3 and RsmA4 for the majority of our studies.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…; Table ). We also observed that mutation of the rsmA1 gene alone did not affect GABA utilization, protease activity and pyoverdine production (except a minor increase in motility) (Figs and ), suggesting that RsmA1 plays a very minimal role, as previously reported (Ferreiro et al , ). Based on these results, we mainly focused on RsmA2, RsmA3 and RsmA4 for the majority of our studies.…”
Section: Resultssupporting
confidence: 87%
“…RsmA (CsrA) plays a critical role in virulence among many pathogenic bacteria (Ancona et al , ; Andrade et al , ; Barnard et al , ). It has been reported that deletion of a single csrA gene in Pst DC3000 did not affect virulence, but bacterial growth was reduced in the csr2 and csr3 mutants (Ferreiro et al , ). In our study, we confirmed that deletion of a single rsmA gene did not change its ability to cause disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations